Characterization and Frequency of Histological Changes in Bovine Livers from Slaughterhouses in Brazil kept on Brachiaria spp. - Araújo, Rebekah Rank; Pupin, Rayane Chitolina; Madureira, Renata Cunha; Morais, Luiz Gustavo de; Quevedo, Lucas de Souza; Lemos, Ricardo Antônio Amaral de; Schild, Ana Lúcia; Colodel, Edson Moleta; Castro, Márcio Botelho de (Acta Scientiae Veterinariae, 2017)
Background: Brachiaria spp. is the main pasture for ruminant productions in Brazil, but the limiting factor for its use is the toxicity due to the presence of steroidal saponins. Chronic ingestion of Brachiaria spp. by cattle may cause liver changes such as fibrosis, bile duct proliferation and clusters of foamy macrophages in the hepatic parenchyma. The main objective of the present study was to evaluate the most frequent histological changes and their frequencies in livers collected in abattoirs in Brazil from beef cattle raised exclusively on Brachiaria spp. and compare them with those observed in animals kept in Andropogon spp. grass and native pastures in Rio Grande do Sul. Materials, Methods & Results: Liver samples without macroscopic changes were collected in abattoirs from 561 healthy Nelore and Nelore crossbred cattle raised in Brachiaria spp. pastures from Mato Grosso (MT), Mato Grosso do Sul (MS), Minas Gerais (MG) and Pará (PA) States. Liver samples from 84 Angus cattle (Bos taurus) kept on native pastures in Rio Grande do Sul (RS) and from 60 Nelore and Nelore crossbreed cattle raised in Andropogon spp. pastures in Tocantins State (TO) were collected as control. Semi-quantitative analysis of the histopathological changes were proceeded: (-) = no change; (+) = slight or discreet change; (++) = moderate change and (+++) = marked change. The main histopathological changes evaluted in the liver samples were the presence of foamy macrophages and its location, parenchymal fibrosis and its location, proliferation of bile ducts, periportal mononuclear infiltrate, presence of crystals in macrophages and within the bile ducts. Foamy macrophages clusters in the liver parenchyma were the most frequent histological changes exclusively observed in samples of animals kept in Brachiaria spp. and it was more frequent in cattle from MS State (P < 0.0001). The periportal hepatic fibrosis was another relevant finding in cattle kept in Brachiaria spp. and was also more frequent in MS animals (P ≤ 0.0001), and was not present in control groups. Proliferation of the bile ducts rate was similar between animals raised in Brachiaria spp. (P > 0.05), though it was higher in cattle kept on native pasture in RS (P < 0.0001). The mononuclear periportal inflammatory infiltrate was more frequent in MS and MG samples than in MT and PA (P < 0.0002). Discussion: The most significant histopathological changes observed in liver samples of cattle from the states of MT, MS, PA and MG kept in Brachiaria spp. pastures from the birth to slaughter, was the presence of foamy macrophages in quantities and variables distribution showing the strengthen association between clusters of foamy macrophages in the liver parenchyma and grazing on this grass. These macrophages could be found in healthy animals kept in Brachiaria spp. pastures and in intoxicated animals. This change was considered frequent and characteristic in animals kept in pastures containing steroidal lithogenic saponins in its composition, and it was frequently observed in ruminants that growed in Brachiaria spp. pastures. Beef cattle kept in Andropogon spp. grass pastures in the state of Tocantins and native pastures in Rio Grande do Sul did not showed foamy macrophages in liver samples. On the other hand, in susceptible sheep kept in Andropogon spp. grass pastures that contains low amount of lithogenic steroidal saponins, are insufficient to induce toxicity and morphological changes in the liver, including aggregates of foamy macrophages.